Novel Gene Fusions in Glioma Tumor Tissue and Matched Patient Plasma. (16th November 2020) - Yekula, Anudeep; Wang, Lan; Muralidharan, Koushik; Small, Julia; Rosh, Zachary; Kang, Keiko; Carter, Bob S; Balaj, Leonora
Abstract: INTRODUCTION: Recent large scale genomic and transcriptomic sequencing analysis has shed light on the heterogeneous molecular landscape of glioblastoma (GBM), unveiling a subset of tumors with gene fusions. As tissue biopsy is highly invasive, limited by sampling frequency and incompletely representative of intra-tumor heterogeneity, liquid biopsy strategies can provide a minimally invasive alternative to diagnose and monitor tumor specific molecular aberrations in patient biofluids. Circulating extracellular vesicles (EVs) are stable lipid sacs that carry genetic material including RNA. The utility of EV RNA based fusion transcript characterization has never been explored before. METHODS: We performed targeted fusion transcriptome profiling of GBM tumor RNA and EV RNA extracted from 2 ml of matched plasma from n = 9 patients with GBM and n = 10 healthy controls. We used QIAseq Targeted RNAscan Human Oncology Panel to screen tumor tissue and EV RNA for fusion transcripts. RESULTS: We detected previously reported oncogenic fusions (FGFR3-TACC3, AGK-BRAF) as well as novel fusions including VTI1A-TCF7L2 and SND1-TMEM178B in tumor tissue with a 100% concordance between RNA-seq analysis and MGH Solid fusion assay. Interestingly, RNA-seq analysis revealed a clustering of fusion transcripts in tumors of patients (n = 3) with fusions (reported by MGH Solid fusion assay). We detected 5 novel fusions in the matched plasma of GBM patients (FGFR3-TACC3, VTI1A-TCF7L2, TMEM91-TAL1, CRTC1-ABHD12, RAB7A-FOXP1). Fusion transcripts FGFR3-TACC3 and VTI1A-TCF7L2 were detected in both tissue and matched plasma. Fusion transcripts detected in healthy controls mostly contained gene domains involved in usual hematopoietic pathways. TMEM91-TAL1 was the only fusion transcript commonly reported in both patient and healthy control plasma. Longitudinal follow up of patient P2 with an FGFR3-TACC3 positive glioma, revealed the potential of monitoring RNA fusions in plasma. CONCLUSION: We report a sensitive RNA-seq based liquid biopsy strategy to detect RNA level fusions in plasma of GBM patients.This proof-of-principle study demonstrates the feasibility of utilizing targeted RNA-seq for fusion transcript profiling of EV RNA derived from plasma of patients with GBM.